AB050. Prognostic relevance of preoperative platelet-to-albumin ratio in patients with upper urinary tract urothelial carcinoma - Zhao, Hongda (Transl Androl Urol, 2017)
BACKGROUND: The aim of this study is to assess the value of platelet-to-albumin ratio on overall survival (OS) and cancer specific survival (CSS) in patients with upper urinary tract urothelial carcinoma (UTUC). METHODS: We retrospectively evaluated 169 patients’ clinicopathological data. The Kaplan-Meier analysis was used to assess the OS and CSS and test the equivalences of the curves by log-rank tests. Univariate and multivariate survival analyses were carried out using Cox proportional hazards regression model. RESULTS: Platelet-to-albumin ratio (PAR) was significantly associated with OS and CSS. Multivariate analyses revealed that PAR was an independent prognostic factor in patients with UTUC. Patients with high PAR value had a higher probability of OS and CSS, compared to patients with low PAR. CONCLUSIONS: The platelet and serum albumin level are low cost and easy to obtain, PAR may be a useful independent prognostic factor in patients with UTUC.